Ibuprofen versus fosfomycin for uncomplicated urinary tract infection in women: randomised controlled trial. (23rd December 2015) - Gágyor, Ildikó; Bleidorn, Jutta; Kochen, Michael M; Schmiemann, Guido; Wegscheider, Karl; Hummers-Pradier, Eva
Abstract : Study question  Can treatment of the symptoms of uncomplicated urinary tract infection (UTI) with ibuprofen reduce the rate of antibiotic prescriptions without a significant increase in symptoms, recurrences, or complications? Methods  Women aged 18-65 with typical symptoms of UTI and without risk factors or complications were recruited in 42 German general practices and randomly assigned to treatment with a single dose of fosfomycin 3 g (n=246; 243 analysed) or ibuprofen 3×400 mg (n=248; 241 analysed) for three days (and the respective placebo dummies in both groups). In both groups additional antibiotic treatment was subsequently prescribed as necessary for persistent, worsening, or recurrent symptoms. The primary endpoints were the number of all courses of antibiotic treatment on days 0-28 (for UTI or other conditions) and burden of symptoms on days 0-7. The symptom score included dysuria, frequency/urgency, and low abdominal pain. Study answer and limitations  The 248 women in the ibuprofen group received significantly fewer course of antibiotics, had a significantly higher total burden of symptoms, and more had pyelonephritis. Four serious adverse events occurred that lead to hospital referrals; one of these was potentially related to the trial drug. Results have to be interpreted carefully as they might apply to women with mild to moderate symptoms rather than to all those with an uncomplicated UTI. What this paper adds  Two thirds of women with uncomplicated UTI treated symptomatically with ibuprofen recovered without any antibiotics. Initial symptomatic treatment is a possible approach to be discussed with women willing to avoid immediate antibiotics and to accept a somewhat higher burden of symptoms. Funding, competing interests, data sharing  German Federal Ministry of Education and Research (BMBF) No 01KG1105. Patient level data are available from the corresponding author. Patient consent was not obtained but the data are anonymised and risk of identification is low. Trial registration No  ClinicalTrialGov Identifier NCT01488955 .